Geographical Analysis of Protected Agriculture in the Abu Zahia Area, Sirte Municipality: A Study in Agricultural Geography (Journal of Libya for geographical studies, 2025)
This study aims to conduct a geographical analysis of the natural and human geographic factors and their impact on protected agriculture. It also focuses on identifying the most important crop types, the cultivated area, and production quantity, with the goal of optimizing the investment in this type of agriculture to ensure food security and support the local economy in the Abu Zahia area, which covers an area of 9,730 hectares and has an estimated population of 8,598. The study adopts the regional approach to clarify the spatial distribution of greenhouses and plastic tunnels and their production quantities. It also applies the descriptive approach, along with two main frameworks: the functional approach, which focuses on the functional structure of the economic activity by studying the agricultural production unit, its tools, labor level, marketing outlets, and daily work movement; and the deterministic approach, commonly used in agricultural geography research to study geographic factors influencing protected agriculture.Furthermore, the study employs the crop-based approach to analyze the types of crops grown in protected agriculture, and the analytical method that relies on numerical data for accurate analysis and comparison. It uses statistical methods to provide a descriptive and analytical picture of the data by extracting ratios and applying certain statistical standards. The study also utilizes Geographic Information Systems (GIS) to produce maps using ArcMap 10.1.
Keywords: Protected agriculture; geographic factors; crops; agricultural production; Abu Zahia area